News Values in Feminine Magazines - Dillon, Alfredo José (2011)
The aim of this paper is to analyze how women’s magazines build their agendas. The point of departure of this investigation is the news values theory, one of the main contributions of the newsmaking studies. Our objective is to corroborate the possible existence of “feminine news values”, by comparing the frames and the models of women that prevail in two Argentinean women’s magazines from the decade of 1990’s (Para Ti and Mujeres & Compañía). We intend to rethink the newsworthiness criteria in feminine journalism and to gather the main issues in these magazines’ pages, where the feminine universe seems to be defined by maternity, marriage, sex, work, fashion, beauty, domestic tasks, etc.